Student Motivation in Learning Physical Education Based on The Implementation and Utilization of Learning Media - Damar Hafidz Alfahri; Ani Pristiawati; Aep Rohendi (Journal of Physical and Outdoor Education, 2025)
This study aims to describe students' learning motivation in physical education learning based on the implementation and utilization of learning media at SMP PGRI I Cimahi,. The research method used is descriptive qualitative with three eighth grade female students as subjects. Data collection techniques include observation, interviews, and documentation, while data analysis is carried out with the help of the NVivo program through the stages of data collection, data reduction, data display, and conclusions. The results of the study indicate that the use of varied and interesting learning media greatly influences students' learning motivation, characterized by an increase in students' desire to succeed, creating a higher motivation to learn, and building students' hopes and ideals for the future. In addition, learning media is also able to create a conducive learning environment and more enjoyable learning activities. when learning uses varied media. Students show high enthusiasm for audio-visual learning media packaged in the form of interactive games. The conclusion of this study is that the use of appropriate learning media can have a positive impact on students' learning motivation in physical education, so teachers are advised to continue to innovate in designing learning media so that the teaching and learning process becomes more effective.